Os antecedentes religiosos na intenção de retransmitir arquivos pdf. - Katsuyama, Fábio Marra (2023)
The intent of relaying digital products is common practice among online consumers. The individual's social extrinsic religious behavior directs the practice. This research understood the mediation of the normative consciousness and permissibility to corruption of the individual's social extrinsic religious in the intention to retransmit books, handouts, and e-books in PDF format. Through structural equation modeling in quantitative survey with 343 respondents the study reveals the permissibility to corruption as a mediator of social extrinsic religiosity in the attitude of retransmission of books, handouts, and e-books in PDF format.